2016
DOI: 10.1139/cjps-2015-0276
|View full text |Cite
|
Sign up to set email alerts
|

The performance of dayneutral strawberries differs between environments in Ontario

Abstract: The strawberry production season can be extended in Ontario if plantings are protected from adverse weather conditions. At present, dayneutral cultivars developed in California are used for production, but are not well adapted to Ontario conditions. The objectives of this study were to determine suitable dayneutral cultivars for production throughout Ontario and to investigate how they react to high tunnel environments. Two sets of trials were run. The first set, planted in 2005 and harvested in 2005-2006, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Strawberry fruits exposed to high relative humidity often suffer from several diseases such as grey mold (Botrytis cinerea), stem-end rot (Gnomoniopsis fructicola), powdery mildew (Podospharea aphanis), and black spot (Colletotrichum acutatum). Strawberry plants also produce fewer and smaller fruits under high temperature condition (Taghavi et al, 2016). It was reported that up to 50% of the ripe fruits can be affected by these diseases (Menzel et al, 2016a;Menzel et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Strawberry fruits exposed to high relative humidity often suffer from several diseases such as grey mold (Botrytis cinerea), stem-end rot (Gnomoniopsis fructicola), powdery mildew (Podospharea aphanis), and black spot (Colletotrichum acutatum). Strawberry plants also produce fewer and smaller fruits under high temperature condition (Taghavi et al, 2016). It was reported that up to 50% of the ripe fruits can be affected by these diseases (Menzel et al, 2016a;Menzel et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Plants were hand-planted in multiple rows on raised beds covered with 1.0 mil black polyethylene mulch with irrigation tape (Netafilm "Streamline" drip tubing at 0.9 L h −1 per emitter at 30 cm spacing) installed under the mulch and the plants were irrigated daily for 1 h during the cropping season. 4 The last noted harvest occurred in late August and regular maintenance regime ceased as the plants began to enter the dormancy phase. Any reproductive organs on the plants were removed before selecting the plants for the current study.…”
Section: Field Experimentsmentioning
confidence: 99%
“…19,71,72 Strawberry cultivars such as "Albion" perform poorly during erratic temperature fluctuations in late fall. 4 We used "Albion" as a model to underpin the efficacy of TRP applied as ground drench or ground drench combined with foliar spray to the plants that were preprogrammed to enter dormancy. We hypothesized that TRP application and subsequent indoleamine metabolism might mitigate the naturally occurring dormancy driven by abiotic stress conditions (low light and cold temperature) and probably extend the developmental phase to yield fruit in November when no fruits are produced in the field conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations